The Fundamental Character of Socioeconomic Exploitation: Human Nature, Technology, Social Institutions, and Ideology. Issue 4 (2nd October 2019) - Wisman, Jon D.
Abstract: Although the concept of socioeconomic exploitation often appears in heterodox economics, its use varies considerably and it is seldom given a well-developed conceptual foundation. The project of this article is to propose a foundation by drawing upon our species' history to uncover exploitation's causes and dynamics. Socioeconomic exploitation exists where political or economic power is used by some to gain advantage at others' expense. Its root force is found in human biology, the fact that as a socially-reproducing species, humans compete for mates, and exploitation of others can generate a competitive advantage. Social institutions direct and channel this competitiveness. Accordingly, during 97–98 percent of our species' existence, competitiveness was not expressed by accumulating material wealth and political power, but by being good warriors and foragers, being cooperative, and being generous. Socioeconomic exploitation accompanied the rise of civilization and the state, when metal-based weaponry enabled a few to gain control over society and ownership and control over the means of production, subjugating all others and appropriating their surplus. Although violence stood behind this exploitation, ideology served as the principal political tool for its maintenance. It is the force of ideology that clarifies why, even with free speech, free press, free assembly, and the franchise, exploitation continues to exist.